1997
DOI: 10.1111/j.1399-6576.1997.tb04831.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative hypnosis reduces postoperative vomiting after surgery of the breasts

Abstract: Preoperative relaxation and/or hypnotic techniques in breast surgery contribute to a reduction of both PONV and postoperative analgesic requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 8 publications
1
36
0
2
Order By: Relevance
“…113,114 Hypnosis has also been found effective when compared with placebo (IIIB). 115 Although some earlier reports suggested that ginger root might have a beneficial effect for PONV prophylaxis, this has not been confirmed in a recent meta-analysis (IIA). 116 …”
Section: Non-pharmacological Techniquesmentioning
confidence: 67%
“…113,114 Hypnosis has also been found effective when compared with placebo (IIIB). 115 Although some earlier reports suggested that ginger root might have a beneficial effect for PONV prophylaxis, this has not been confirmed in a recent meta-analysis (IIA). 116 …”
Section: Non-pharmacological Techniquesmentioning
confidence: 67%
“…Two articles were excluded because they included women undergoing elective breast surgery. 25,26 Another article was excluded because it was not randomized. 27 Thirteen RCTs with a total of 1357 patients were included in the review.…”
Section: Literature Searchmentioning
confidence: 99%
“…Three hundred and thirty-three records were retrieved in literature search, and 16 full-text articles were assessed for eligibility [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ( Figure 1). Two articles were excluded because they included women undergoing elective breast surgery.…”
Section: Literature Searchmentioning
confidence: 99%
“…In our study, only 2 patients required pharmacological therapy for PONV. Previous studies have shown that hypnosis is effective for prevention of nausea and vomiting [1,2,18,19]. All 15 patients in our study also had smooth postoperative course and reported complete amnesia for intra-operative events.…”
Section: Discussionmentioning
confidence: 52%